Pengembangan Media Construct 2 dalam Pembelajaran Qira’ah di Madrasah Tsanawiyah Negeri 1 Yogyakarta - Habibur Rohman (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan, 2019)
This research development aims to find out how to make media construct 2 in learning qirā'ah at MTs N 1 Yogyakarta and to find out how students respond to media construct 2. This media research uses the R&D research model of Borg and Gall which consists of 10 steps: potential and problems, data collection, product design, design validation, design revisions, product trials, product revisions, trial usage, product revisions, and mass production. The procedure of this research is limited to the testing phase of usage. This product was reviewed by supervisors, material experts, media experts and peers (peer reviewers) and responded by 31 MTs N 1 Yogyakarta students. The instrument used in the form of a questionnaire to see product quality and student questionnaire responses to see students' responses to the product. Research results and responses in the form of quantitative data, then analyzed with assessment criteria and percentage of ideals to determine product quality. The results of research development in the form of instructional media construct 2. Based on the results of the assessment, according to experts construct media 2 in learning qirā'ah has a very good quality with a percentage of ideals 83.16%. While the response generated according to 31 students is 81.5%. From the results of the assessment, it can be concluded that media construct 2 is feasible and can be used as a learning medium.